Skin manifestations in patients with covid-19: A literature review - Gunawan, Danny; Stella, Maureen Miracle; Sidharta, Veronika Maria (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. In December 2019, cases of pneumonia with unknown cause were first reported in Wuhan, Hubei Province, China. Confirmed cases and death rates due to COVID-19 in the world are still increasing. One part of the body that is affected and causes clinical symptoms in COVID-19 is the skin. This review aims to describe and analyze cutaneous manifestation in COVID-19. This study method is a review of the literature sourced from Google Scholar and PubMed. The literature was selected using English language criteria, using the clinical study method in the form of case reports. Meanwhile, literature review, systematic literature, and meta-analysis were excluded. Journal searches were carried out using the keywords "skin" OR "cutaneous" AND "manifestation" AND "COVID-19" OR "coronavirus". The skin manifestations of COVID-19 have been observed. The most common clinical symptoms of COVID-19 were fever (47%), dry or productive cough (25%), sore throat (16%), generalized sore throat (6%), and pain (5%). However, currently there has been a shift in the approach to diagnosing COVID-19 because it can cause symptoms in other organ systems, one of which is skin manifestations. There are early reports of skin involvement (erythematous rash, extensive urticaria, and chickenpox-like vesicles) occurring in 20% of patients in the course of the COVID-19 disease. In addition, several case reports provide descriptions of petechiae and chilblains. Based on the cases that have been reported, patients with COVID-19 who have manifestations on the skin can give a picture of maculopapular eruptions, vesicular eruptions, petechiae, and also childblains.